2020
DOI: 10.1093/cercor/bhaa013
|View full text |Cite
|
Sign up to set email alerts
|

Syndapin I Loss-of-Function in Mice Leads to Schizophrenia-Like Symptoms

Abstract: Schizophrenia is associated with cognitive and behavioral dysfunctions thought to reflect imbalances in neurotransmission systems. Recent screenings suggested that lack of (functional) syndapin I (PACSIN1) may be linked to schizophrenia. We therefore studied syndapin I KO mice to address the suggested causal relationship to schizophrenia and to analyze associated molecular, cellular, and neurophysiological defects. Syndapin I knockout (KO) mice developed schizophrenia-related behaviors, such as hyperactivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 72 publications
0
40
0
Order By: Relevance
“…Primary rat hippocampal neuronal cells for immunofluorescence analyzes were cultured and maintained as described previously [ 30 , 31 , 32 ]. Briefly, neurons dissociated from hippocampi of E18 rats were seeded at a density of 60,000/well (24-well plate).…”
Section: Methodsmentioning
confidence: 99%
“…Primary rat hippocampal neuronal cells for immunofluorescence analyzes were cultured and maintained as described previously [ 30 , 31 , 32 ]. Briefly, neurons dissociated from hippocampi of E18 rats were seeded at a density of 60,000/well (24-well plate).…”
Section: Methodsmentioning
confidence: 99%
“…In the DEGs screening of CGGA and GSE4290 datasets between the tumour group and the normal group, we obtained the gene PACSIN1 and found that it significantly downregulated in gliomas (Figures 1A,B). Previously, PACSIN1 was only recognized to affect neurons development and nervous system regulation (Pérez-Otaño et al, 2006;Gopalakrishnan et al, 2016;Koch et al, 2020), and its relationship with tumours or even gliomas has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…However, its role and function in tumours are still unclear. So far, many studies have found that PACSIN1 plays an essential role in developing of neurons and the regulation of the nervous system (Pérez-Otaño et al, 2006), and the inappropriate expression of PACSIN1 can even lead to Huntington's disease, schizophrenia and other neurological diseases (Gopalakrishnan et al, 2016;Koch et al, 2020). Therefore, we hypothesized that PACSIN1 expression is related to the occurrence and development of gliomas.…”
Section: Introductionmentioning
confidence: 97%
“…The brains were quickly removed and separated into two parts using a Precision Brain Slicer (Braintree Scientific Inc.) at bregma +0.8 mm using the Allen Brain Atlas as reference. The anterior part was used for the 25 infarct validation by anti-MAP2 staining (see below), and the posterior part was used for Golgi-Cox staining using FD Rapid GolgiStain kits (FD NeuroTechnologies, Inc), essentially following a protocol described previously (Schneider et al, 2014; Koch et al, 2020). In brief, the posterior brain part was immersed in solution A+B of the FD Rapid GolgiStain kit and kept in the dark at RT for 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…Three-dimensional reconstructions of neuronal morphologies were performed with Imaris 8.0 software (Bitplane) using the filament tracer set with shortest distance algorithm (diameter: 2-16 µm). The images were baseline- and background-subtracted as described before (Koch et al, 2020). As in previous software-based quantitiative determinations of dendritic arbor complexity evaluations (Izadi et al, 2018) the following parameters were analyzed: the number of Sholl intersections, the number of dendritic branching points, the numbers of dendritic terminal points and the total dendritic tree length.…”
Section: Methodsmentioning
confidence: 99%